'One cigarette for you and one for me': children of smoking and non-smoking parents during pretend play. Issue 5 (18th February 2011) - de Leeuw, Rebecca N H; Verhagen, Maaike; de Wit, Cindy; Scholte, Ron H J; Engels, Rutger C M E
Abstract : Objective: To investigate whether perceived parental smoking is related to pretend smoking in young children and whether children influence each other in pretend smoking. Methods: Children who reported to have at least one smoking parent were coupled with children who had non-smoking parents. Both children were then asked to pretend that they were adults having a barbeque party. During their role playing, the children were observed in order to assess their pretend smoking behaviours and to examine whether children of smoking parents were more likely to initiate pretend smoking. Children were tested at their schools; the sample consisted of 206 children between 4 and 7 years of age (mean age=5.14, SD=0.87), of which 54.4% were girls. The main outcome was whether a child pretended to be smoking and whether the child initiated or followed the other child in this behaviour. Results: During their play, 63.6% (n=131) of the children pretended to smoke. Children of smoking parents were more likely to initiate pretend smoking than to follow. Conclusions: Through their own smoking, parents appear to be able to influence the way in which their children interact with peers regarding pretend smoking. More specifically, children of smoking parents might instigate smoking among their peers.